2014
DOI: 10.1021/am4049139
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Characterization of TiO2 Films Grown by Atomic Layer Deposition on RuO2 Electrodes

Abstract: Topography and leakage current maps of TiO2 films grown by atomic layer deposition on RuO2 electrodes using either a TiCl4 or a Ti(O-i-C3H7)4 precursor were characterized at nanoscale by conductive atomic force microscopy (CAFM). For both films, the leakage current flows mainly through elevated grains and not along grain boundaries. The overall CAFM leakage current is larger and more localized for the TiCl4-based films (0.63 nm capacitance equivalent oxide thickness, CET) compared to the Ti(O-i-C3H7)4-based fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
1
17
0
1
Order By: Relevance
“…In agreement with a previous literature report, the thickness of the TiO 2 on top of underlayer grain boundaries is larger and at the grain tips is smaller. 25 Before steam treatment, at the Cu 2 O grain boundaries (represented in red in Fig. 7c) the TiO 2 is thicker than at the grain tips with an average difference of 26 nm.…”
Section: Resultsmentioning
confidence: 98%
“…In agreement with a previous literature report, the thickness of the TiO 2 on top of underlayer grain boundaries is larger and at the grain tips is smaller. 25 Before steam treatment, at the Cu 2 O grain boundaries (represented in red in Fig. 7c) the TiO 2 is thicker than at the grain tips with an average difference of 26 nm.…”
Section: Resultsmentioning
confidence: 98%
“…For example, it has been shown that, in a microstructure composed of small TiO2 nanorods, carriers exhibit lower mobility than in large crystallites [28]. Moreover, interestingly, Murakami et al have investigated out-plane electrical properties combining macroscale current-voltage characteristics and conductive atomic force microscopy (C-AFM) mapping to show that conduction occurs through grains and that current magnitude depends on the precursor nature for ALD processed rutile-TiO2/RuO2 stacks [29].…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…Additionally, there is conflicting information about the temperature of the ALD window, the GPC at each temperature, 18−21 and the self-saturation of the precursors. 11,20,21 There have been no studies on how precursor pressure affects the reactivity of the surface species. These problems illustrate the lack of fundamental understanding of the surface chemistry for this system.…”
Section: ■ Introductionmentioning
confidence: 99%